3x+4+2x-12=3(x+2)

Simple and best practice solution for 3x+4+2x-12=3(x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+4+2x-12=3(x+2) equation:



3x+4+2x-12=3(x+2)
We move all terms to the left:
3x+4+2x-12-(3(x+2))=0
We add all the numbers together, and all the variables
5x-(3(x+2))-8=0
We calculate terms in parentheses: -(3(x+2)), so:
3(x+2)
We multiply parentheses
3x+6
Back to the equation:
-(3x+6)
We get rid of parentheses
5x-3x-6-8=0
We add all the numbers together, and all the variables
2x-14=0
We move all terms containing x to the left, all other terms to the right
2x=14
x=14/2
x=7

See similar equations:

| -5.6=h5+12.2 | | 0.095*x=1.61 | | 5x-2x+x=9 | | -11.55=2.4x+12.45 | | X+(1/2)x+4=10 | | 4(x–1)=8x-40 | | 2^5=8^5x | | 7+9q=4q-8 | | 1x+2x-21=90 | | 16=b/21 | | -1/2w+3/5=1/6 | | 45=y/9+38 | | 3(x-2)=x-76 | | 2x+7=-5* | | 6(2y-5)=-(y+4) | | h+87=848 | | 41=-1-8k | | 8(12x-5)-16=40 | | 5x-51=8x-30 | | 9−3m/3=2m | | 64.4x=29,817 | | 3x+58=94 | | -11+x=-2 | | -3x+(-3)+5x=15 | | 4x+7x=10x+8 | | 3(x-7)-1=2 | | 2(x-2)=6x-3 | | 6-h=-8-3h | | -6m-12=-60 | | -2(7x-12)=-88 | | g+109=4 | | 1/3x-8=-15 |

Equations solver categories